Identification of gene mutations associated with type 1 diabetes by next-generation sequencing in affected Palestinian families - Bawatneh, Abrar; Darwish, Alaa; Eideh, Hasan; Darwish, Hisham M. (Frontiers in Genetics, 2024)
Diabetes Mellitus is a group of metabolic disorders characterized by hyperglycemia secondary to insulin resistance or deficiency. It is considered a major health problem worldwide. T1DM results due to a combination between genetics, epigenetics, and environmental factors. Several genes have been associated with T1DM including HLA, INS, CTLA4, and PTPN22. However, none of them was based on linkage analysis because it's rare to find families with several diabetic individuals. Two Palestinian families with several inflicted members with variations in the mode of inheritance were identified and selected for this study. The Aim of this study was to identify putative causative gene(s) responsible for T1DM development in these families to improve our understanding of the molecular genetics of the disease. One inflicted member from each family was selected for Whole-Exome Sequencing. Data were mapped to the reference human genome and the resulting VCF file data was filtered. The variants with the highest phenotype correlation score were checked by Sanger sequencing in all family members. The confirmed variants were in-silico analyzed by bioinformatics tools. In one family, IGF1R p.V579F variant which follows autosomal dominant inheritance was confirmed and segregated in the family. In another family, NEUROD1 p.P197H variant which follows autosomal recessive inheritance was positively confirmed and segregated. In conclusion, IGF1R p.V579F and NEURID1 p.P197H variants were associated with T1DM development in the two inflicted families. Further analysis and functional assays will be performed including the generation of mutant model cell system to unravel their specific molecular mechanism in the disease development.